Extremely-low electrical-hysteresis hydrogels for multifunctional wearable sensors and osmotic power generators - Entifar, Siti Aisyah Nurmaulia; Entifar, Nisa Aqilla Ellenahaya; Wibowo, Anky Fitrian; Kim, Jung Ha; Shara, Yulia; Saputro, Jonatan Martino Windi; Kim, Han-Gyeol; Kim, Jong-Oh; Xie, Guohua; Oh, Junghwan; Kim, Soyeon; Lim, Dong Chan; et al. (Elsevier BV, 2025)
In this study, a highly stretchable and conductive hydrogel film composed of carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), and poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) was developed for application in wearable sensors, machine learning-based activity recognition, and hydrovoltaic energy generation. The optimized hydrogel exhibited a tensile strength of 0.391 MPa, an elongation at break of 303.8 %, a toughness of 0.525 MJ/m(3), a conductivity of 2.04 S/m, and a low electrical hysteresis of 0.101 % at 50 % strain. With a gauge factor of 1.034, the hydrogel accurately detected human motions and achieved 100 % classification accuracy in classifying movements using machine learning. In hydrovoltaic applications, 16 films connected in series generated 2.01 V, powering a light-emitting diode lamp. These results highlight the potential of the CMC-PVA-PEDOT:PSS-based hydrogel for next-generation wearable electronics and sustainable energy systems.